Stability and Related Thermodynamics of Chelation of Fe(II), Co(II), Ni(II) and Cu(II) Metal Ions with Diacetyl-bis-(4-methoxybenzoylhydrazone) - K. Jha, Ashok; K. Roy, Ramesh; S. Jha, Chandra (Asian Journal of Chemistry, 2010)
Chelate formation of Fe(II), Ni(II), Co(II) and Cu(II) with diacetyl bis-(4-methoxybenzoylhydrazone) in water-dioxane (1 : 1) at constant ionic strength (0.1 M KNO3) and at three different temperatures 20 ± 0.1 °c, 30 ± 0.1 °c and 40 ± 0.1 °c have been studied potentiometrically. The proton-ligand and metal-ligand stability constants were determined by Irving-Rossotti pH-metric titration technique. Thermodynamic functions ΔG, ΔH, ΔS and ΔCp were evaluated by making the investigations at three different temperatures. The order of stability constant with respect to metal ions followed the natural order.